Caprellidae (Crustacea: Peracarida: Amphipoda) from deep-sea waters off Galicia (NW Iberian Peninsula) with the description of a new genus and three new species - Guerra-García, José M.; Tato, Ramiro; Moreira, Juan (Zootaxa, 2018)
The Caprellidae (Crustacea: Amphipoda: Senticaudata) from the upper continental slope of Galicia (NW Iberian Peninsula) was studied. The material collected, based on surveys conducted from 2002 to 2009, comprised 11 species. A new genus Selvacaprella gen. nov., and three new species Selvacaprella jimenoi sp. nov., Liropus vitucoi sp. nov. and Liropus willyi sp. nov. are described. Pedoculina cf. bacescui and Parvipalpina cf. verrucosa are also figured in detail. Parvipalpina cf. verrucosa and Caprella cf. ciliata enlarge their distribution range ca. 2000 km to the South. Pedoculina cf. bacescui represent the first record of the genus for the Atlantic. These three species are also first records for the Iberian Peninsula. The total number of known caprellid species in the Iberian Peninsula (including adjacents waters of Ceuta, Canary Islands, Balearic Islands, Azores and Madeira) is 50 so far, making this area one of the most diverse in the world for this group of amphipods.